Effects of Camphor on Sexual Behaviors in Male Rats: Effects of camphor on sexual behaviors - Jamshidzadeh, Akram; Tavakoli, Fateme; Sajedianfard, Javad; Nekooeian, Ali Akbar; Omrani, Gholam-Hossein (Iranian Journal of Pharmaceutical Sciences, 2006)
According to Iran’s folk medicine, camphor, a crystalline ketone obtained from essential oils of Cinnamomum camphora, has both sexual behavior attenuating and enhancing properties. This study examined the effects of camphor on sexual behavior in male rats. Twenty four sexually mature male Sprague-Dawley rats were randomly divided into 4 groups receiving daily i.p. injections of olive oil as vehicle (2.5 ml/kg) or camphor at 2.5, 12.5 or 50 mg/kg for 7 days. Afterwards, mount latency (ML), mount frequency (MF), intromission latency (IL) and intromission frequency (IF) of male rats in the presence of sexually receptive females rats were recorded. There was no significant difference in MF or IF from control and experimental groups. However, at the 50 mg/kg dose, camphor reduced the ML and IL relative to that of control rats. The finding indicates that at this dose, camphor had sexual desire and sexual performance enhancing properties.